The Jewish Museum in Vilnius: The First Attempts to Give Meaning to Traumatic Experience and Promote Sustainable Memory - Latvytė-Gustaitienė, Neringa (Knygotyra, 2018)
[full article and abstract in Lithuanian; abstract in English] The Jewish Museum in Vilnius, founded in the autumn on 1944 upon the initiative of the Holocaust survivors, played a special place in the collective memory of Litvaks. It was the first and unique attempt in Eastern Europe to (publicly) present the massive killings of Jews by the Nazi and local collaborators, primarily by shooting, and by annihilating themat Nazi concentration camp gas chambers, the plunder of cultural and spiritual values, and the efforts of survivors to collect and preserve Jewish heritage remnants. The museum became a certain genius loci, that is, a lively place giving both material and mental meaning to the Jewish community, creating emotions, providing a certain sense of security and encouraging dialogue. Unfortunately, the Soviet government failed to understand the uniqueness of the museum and appreciate the importance of its activities. This memory institution was closed down in 1949, in the midst of an anti-Semitic campaign. The collections and exhibits accumulated in the museum were distributed to Lithuanian museums, archives and libraries. Thus, the Jewish history, culture and traditions and the very theme of mass murder of the Jews were pushed to the margins of history for the period of 40 years. (De)codable with double-memory standards, the so-called counter-memory of kitchen communities or reprocessed memory was rather wretchedly presented in public were maintained as a counterweight to the hegemonic narrative. It was under the influence of the latter that in September of 1989 the Lithuanian State Jewish Museum was restored. The first exhibition named “Catastrophe”, mounted in the newly restored museum, was the only Holocaust exhibition in the former Soviet bloc countries. Later it was granted the status of a separate museum branch, called the Holocaust exposition. Renovated in 2010, the exhibition has retained the features of the post-war Jewish Museum exhibition. As such, it attracts a lot of visitors and encourages sustainable memory. The aim of the article is to introduce the circumstances related to the establishment of the post-war Jewish Museum in Vilnius, distinguishing its peculiarities by demonstrating the attempts and methods of the Holocaust survivors to publicly introduce the traumatic experiences of the community, as opposed to the discourse shaped by the Soviet regime, as well as showing the exclusivity of the memory institution itself in today’s society.